Schematy fabularne w filmach Nighta M. Shyamalana. Mit - bajka - komiks = Plot patters in the movies of Night M. Shyamalan. Myth - tale - comic strip - Kulczycka, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of this article takes up the issue of the connections between the movies of the Indian-American film director-screenwriter-producer (and actor) and literature. There are some aspects andlevels of these intra-film/textual and outside-film/textual inclinations. What is particularly significant,especially for "Unbreakable" and "Lady in the Water", are intersemiotic games with the myth, the fairytale, as well as with bedtime stories, magic tales and twentieth-century comic strips.
Keywords: Shyamalan, Manoj Nelliyattu (hinduski reżyser; 1970- ); adaptacja filmowa